Turning metaphor on its head: a “target-to-source transformation” approach in statistics education - Tay, Dennis (Frontiers in Psychology, 2023)
Many practical applications of metaphors are based on the idea that they are static TARGET IS SOURCE structures that support unidirectional meaning transfer for various purposes. Examples include healthcare and education where metaphors build cognitive and communicative bridges between the abstract and concrete. However, real-world metaphor use is often more dynamic than static, raising the question of how practical applications could benefit from a more correspondingly dynamic perspective. Drawing upon learning models that view learner output as creative transformations of input, this article introduces a “target-to-source transformation” approach that (i) initially frames concepts unfamiliar to novice learners as metaphorical targets as per received wisdom, but after some time, and (ii) invites learners to transform these targets into source domains for new target domains of their choosing. A pilot implementation is reported in the context of a statistics course, in particular the concept of regression analysis, for humanities students. Examples of transformed metaphors include different aspects of regression as sources for creative targets like “arranging a meeting time for friends,” “finding a life partner,” and “fortune-telling.” Analysis of these examples suggests that the approach creates a sense of pedagogical consistency, allows students to exercise creativity, and gives teachers novel insights into their level of understanding. Points for critical reflection will also be raised for future development of the approach, including the need to consider oft-overlooked metalinguistic attitudes held by laypersons toward metaphors.